ALFABETIZAÇÃO CIENTÍFICA NA EDUCAÇÃO INFANTIL PARA APRENDIZAGEM DOS FENÔMENOS DA NATUREZA - FARIAS, Áurea Selma da Silva (2024)
In daily life, from an early age, children present many questions and questions that need to be clarified. And it is in the coexistence of school that some issues come to be understood. And scientific literacy tends to contribute to the learning of children. The aim of this research was to understand the contribution of scientific literacy in early childhood education to the promotion of learning about the phenomena of nature in a kindergarten school in the county of Bagre in the Marajó, for the contents of science related to the phenomena of nature, such as wind and rain. Initially, a Free and Informed Consent Form was presented to the responsible for children and the authorization for the school. Subsequently, the research was developed, using a qualitative approach, being used as a data collection instrument, a semi-structured script with two questions: Where does the rain come from? and Where does the wind come from? The recording technique was the voice recording made with the mobile application. The target audience were five year olds. The data were obtained through experiments and videos, obtained through Internet sites, In addition, we used features such as music, mockup and drawings in the approach to content. The results showed that 47.6% of the children were able to understand the origin of the wind and its distribution in the physical spaces and 100% could understand the origin of the rain. These results show that scientific literacy can still be inserted in early childhood education. Key words: Scientific literacy. Early childhood education. Fenômenos da natureza.